Perspektif Multibudaya Dalam Bimbingan dan Konseling - Mohammad Rizky Adi Syahputra; Muhammad Yunus Efendi; Bakhrudin All Habsy (Lembag, 2025)
This article discusses the importance of a multicultural approach in guidance and counseling, in a country rich in cultural diversity. Within this context, counselors are expected to understand and appreciate the cultural differences faced by clients, including different values, norms, and perspectives. Multicultural counseling not only increases the effectiveness of the counseling process, but also creates a safe counseling environment for clients to express themselves. By understanding the client's cultural background, the counselor can minimize potential conflicts and increase confidence in the counseling relationship. This research uses a qualitative method with a literature study to explore the challenges and solutions in multicultural counseling practice. The findings of this article suggest that sensitivity to cultural diversity is essential for successful inclusive and responsive counseling.